2020
DOI: 10.15408/ijee.v6i2.12019
|View full text |Cite
|
Sign up to set email alerts
|

Developing EFL Students’ Writing Skill Through Self-Assessment Integrated With E-Portfolio

Abstract: Writing is one of the language skills that should be mastered by students of English as a foreign language (EFL). In order to write well, EFL students should understand the content of their writing. They should also be able to discover some writing errors they may have. Therefore, it is necessary for the students to practice writing frequently and to be willing to review their writing products. This study aimed to develop EFL students’ writing skill through self-assessment integrated with e-portfolio. It used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Assessment rubrics that are in accordance with the basic competencies of subjects do require the teacher's thinking and creativity. This is often an obstacle for teachers in assessing student portfolio work results [41]. A portfolio assessment that is carried out continuously will certainly provide a systematic and periodic track record of student development [12].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment rubrics that are in accordance with the basic competencies of subjects do require the teacher's thinking and creativity. This is often an obstacle for teachers in assessing student portfolio work results [41]. A portfolio assessment that is carried out continuously will certainly provide a systematic and periodic track record of student development [12].…”
Section: Discussionmentioning
confidence: 99%
“…Informal tasks such as reflection and self-assessment are examples of formative assessment activities for learning (rather than grading) design of the e-portfolio by lecturers. The study by Taufik and Cahyono (2019) has suggested that the e-Portfolio develops writing skills through self-assessment. For example, through a reflective journal or diary entry submitted weekly as a self-assessment activity, students can identify errors in their writing, which also helps to master the language and content independently.…”
Section: Discussionmentioning
confidence: 99%
“…The e-Portfolio approach, therefore, fosters autonomy in the learning tasks and promotes intrinsic motivation for learning (Beckers & Merrienboer, 2018). Taufik and Cahyono (2019) have also suggested that the e-Portfolio develops writing skills through self-assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Salah satu aspek perkembangan bahasa yang perlu disiapkan dan dikembangkan pada anak usia dini untuk menghadapi jenjang pendidikan selanjutnya adalah kemampuan mengenal huruf (Firdaus, 2019;Fitriani et al, 2019). Stimulasi keaksaraan pada anak adalah dengan cara menstimulasi anak untuk mengenali dan memahami simbol huruf yang ada di dalam abjad sehingga pada saat memasuki sekolah dasar tidak mengalami kesulitan untuk menguasai keterampilan membaca awal (Rahayuningsih et al, 2016;Taufik & Cahyono, 2020). Pengembangan keaksaraan meliputi berbahasa, menyimak, membaca, dan menulis (Gatot, 2018;Ws et al, 2016).…”
Section: Pendahuluanunclassified